Individual vs. Combined Short-Term Effects of Soil Pollutants on Colony Founding in a Common Ant Species - Seidenath, Dimitri; Holzinger, Anja; Kemnitz, Klara; Langhof, Nico; Lücker, Darleen; Opel, Thorsten; Otti, Oliver; Feldhaar, Heike (Frontiers in Insect Science, 2021)
Insects are integral to terrestrial life and provide essential ecosystem functions such as pollination and nutrient cycling. Due to massive declines in insect biomass, abundance, or species richness in recent years, the focus has turned to find their causes. Anthropogenic pollution is among the main drivers of insect declines. Research addressing the effects of pollutants concentrates on aquatic insects and pollinators, despite the apparent risk of contaminated soils. Pollutants accumulating in the soil might pose a significant threat because concentrations tend to be high and different pollutants are present simultaneously. Here, we exposed queens of the black garden ant Lasius niger at the colony founding stage to different concentrations and combinations of pollutants (microplastic particles and fibers, soot, brake dust, and manure) to determine dose-dependent effects and interactions between stressors. As surrogates for colony founding success, we measured queen survival, the development time of the different life stages, the brood weight, and the number of offspring. Over the course of the experiment queen mortality was very low and similar across treatments. Only high manure concentrations affected the colony founding success. Eggs from queens exposed to high manure concentrations took longer to hatch, which resulted in a delayed emergence of workers. Also, fewer pupa and workers were produced by those queens. Plastic, soot and brake dust particles did not visibly affect colony founding success, neither as single nor as multiple stressors. The application of manure, however, affected colony founding in L. niger negatively underlining the issue of excessive manure application to our environment.